An Early Christian Reaction to Islam: Išū'yahb III and the Muslim Arabs - Bcheiry, Iskandar (Gorgias Eastern Christianity studies, 2019)
Frontmatter -- TABLE OF CONTENTS -- ACKNOWLEDGMENTS -- ABBREVIATIONS -- LIST OF FIGURES AND TABLES -- INTRODUCTION. PATRIARCH IŠŪ'YAHB III'S VIEW OF THE MUSLIM ARABS -- CHAPTER ONE. HISTORICAL BACKGROUND -- CHAPTER TWO. IŠŪ'YAHB III: HIS LIFE, CAREER AND LETTERS -- CHAPTER THREE. IŠŪ'YAHB III AND THE MUSLIM ARABS -- CHAPTER FOUR. PATRIARCH IŠŪ'YHAB'S POSITIVE ATTITUDES TOWARD THE MUSLIM ARABS -- CONCLUSION -- BIBLIOGRAPHY -- INDEX OF PERSONAL NAMES